Interior regularity to the signed solution of the singular doubly nonlinear parabolic equations (Journal of Bangladesh Academy of Sciences, 2023)
We study doubly nonlinear parabolic equation with sign changing solutions. We establish the Hölder regularity of the singular parabolic equations within a parabolic domain.J. Bangladesh Acad. Sci. 47(2); 241-248: December 2023